The Effect of Regulations and Policies on the Development of E-Business in Indonesia - Heri Nurdiyanto; Muhammad Said Hasibuan; Isnandar Agus; faurani santi singagerda (Journal of Research in Social Science and Humanities, 2024)
This paper examines the impact of regulations and policies on the development of e-business in Indonesia. As e-business becomes increasingly integral to the economy, understanding the regulatory environment is crucial for stakeholders, including policymakers, business owners, and consumers. The study explores the current regulatory framework governing e-business in Indonesia, identifying key policies that influence its growth and development. Through qualitative analysis of government regulations, industry reports, and expert interviews, the paper highlights both the supportive and restrictive aspects of these regulations. Findings indicate that while certain policies, such as tax incentives and infrastructure investments, have fostered e-business growth, others, including stringent data protection laws and complex compliance requirements, pose challenges. The research underscores the need for a balanced regulatory approach that promotes innovation while ensuring consumer protection and fair competition. Recommendations are provided for policymakers to enhance the regulatory landscape, suggesting measures such as streamlined compliance processes, enhanced digital literacy programs, and increased collaboration between government and industry stakeholders. Ultimately, this paper aims to contribute to the discourse on how regulations can be optimized to support the sustainable growth of e-business in Indonesia, aligning with broader economic goals and technological advancements.